The Economic of Umar Bin KhattÄb Policyin Modern Economic Policy - Hendri Hermawan Adinugraha (UBL, 2013)
Along with the famous term of the shari’ah economics in Indonesia today, many financial institutionsare using Shari’ah-based system. Ranging from syari’ah banking, syari’ah hotels, syari’ah supermarkets,etc. In fact, it shows the amount of interest in addressing public demand for the implementation ofshari’ah system in financial institutions and businesses. The Islamic economists face big challenges, thatsdisability of shari’ah economics implementation. it is mean the economic policy can not be applied byShari’ah system optimiscally at stage of government policy.The economic of Umar bin Khattāb policy is reasonably as a comparator (comparison tool) becausehe was a proper and powerful head of government in managing the government, he is also a successfulentrepreneur, as well 2nd Kholifah, at which time the majority of its policies relating to the economicradicalization.The purpose of this study was to determine the economic of Umar bin Khattāb policy and analyze itsrelevance to the context of the current economic. The method of analysis is used qualitative study by athematic approach to observe and analyze each Umar bin Khattāb policy which on occasion of economic.Then it is combined with library research by reading the works of Umar economic policy. Dataprocessing techniques is used the content analysis method, to make inferences Umar economic policy.Then analyzed to obtain the relevance of the development policy.The results of this study is indicating that some economic policy during the reign of Umar has beenadopted by most countries in the world with improvement in certain parts in accordance with its time.This suggests that the current economic policy of Umar bin Khattab still relevant if implemented on amodern economy.